418 First-line Stent Retriever Thrombectomy vs Direct Aspiration for Acute Basilar Artery Occlusion: A Systematic Review and Meta-analysis. (1st April 2022) - Texakalidis, Pavlos; Xenos, Dimitrios; Karras, Constantine L.; Murthy, Nikhil; Hopkins, Benjamin; Kontzialis, Marinos; Rivet, Dennis J.; Reavey-Cantwell, John
Abstract : INTRODUCTION: Mechanical thrombectomy (MT) for acute anterior circulation stroke is an already established therapy. Recently, MT has been also increasingly utilized for basilar artery occlusion (BAO); the mainstay of MT modalities are stent retriever (SR) and direct aspiration (DA). Several studies have been recently published comparing the two approaches. METHODS: A systematic review and meta-analysis was conducted according to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. RESULTS: Overall, eight studies comprising 693 patients with acute BAO were included (SR: 457; DA: 236). The SR group was associated with statistically significant lower odds for successful recanalization defined as modified Thrombolysis in Cerebral Infarction (mTICI) 2b/3 (SR:81.9%, DA: 88.2%; OR:0.54; 95%CI:0.31-0.94; I2:0%) and mTICI 3 (SR: 51%, DA: 62.5%; OR:0.47; 95%CI:0.23-0.95; I2:62.1%) compared to DA. Favorable outcome rates defined as modified Rankin Scale (mRS) = 2, were similar between the two groups (SR: 37.8%, DA: 41.9%; OR:0.83; 95%CI: 0.60-1.16; I2:0%). The rates of symptomatic ICH (sICH) were higher in the SR group compared to the DA group (SR: 8.7% vs DA: 0.9%, however statistical significance was not reached OR: 3.57; 95%CI: 0.75-16.95; I2:0%). Similarly, subarachnoid hemorrhage (SAH) (SR: 5%, DA:0%; OR:4.71; 95%CI: 0.82-26.90; I2:0%) and vessel perforation (SR: 3.4%, DA: 1.1%; OR: 2.64; 95%CI: 0.43-16.33; I2:0%) rates were higher in the SR group but again significance was not reached. The rates of 90-day mortality were similar between the two groups (SR: 27.5%, DA: 28.1%; OR: 1.07; 95%CI: 0.67-1.70; I2:0%). Procedure duration was significantly shorter when DA was used compared to SR (WMD: 26.10;95%CI:13.28-38.92; I2:35.3%). CONCLUSION: DA is associated with statistically significant higher odds of successful mTICI 2b/3 and mTICI 3 recanalization rates and shorter procedure duration compared to SR. In addition, in absolute numbers, SR was associated with higher rates of sICH, SAH and vessel perforation, however, statistical significance was not reached most likely due to the relatively low sample size.